2012
DOI: 10.1118/1.4704729
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the geometric accuracy of surrogate‐based gated VMAT using intrafraction kilovoltage x‐ray images

Abstract: Purpose: To evaluate the geometric accuracy of beam targeting in external surrogate-based gated volumetric modulated arc therapy (VMAT) using kilovoltage (kV) x-ray images acquired during dose delivery. Methods: Gated VMAT treatments were delivered using a Varian TrueBeam STx Linac for both physical phantoms and patients. Multiple gold fiducial markers were implanted near the target. The reference position was created for each implanted marker, representing its correct position at the gating threshold. The gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 18 publications
(20 reference statements)
1
47
0
Order By: Relevance
“…16 Recent report evaluated the geometric accuracy of the surrogate-based gated VMAT with a respiratory phantom and also on real patients cases including liver tumors. 17 Li et al showed in a phantom study a high geometric accuracy (average error of 0.8 mm in the CC direction) when no targetsurrogate relation changes occurred during the treatment. However, including a phase shift of 5% and 10% increased the average errors to 2.3 and 4.7 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recent report evaluated the geometric accuracy of the surrogate-based gated VMAT with a respiratory phantom and also on real patients cases including liver tumors. 17 Li et al showed in a phantom study a high geometric accuracy (average error of 0.8 mm in the CC direction) when no targetsurrogate relation changes occurred during the treatment. However, including a phase shift of 5% and 10% increased the average errors to 2.3 and 4.7 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements in the technology of 4‐Dimensional Computed Tomography (4DCT) image binning,15, 16, 17, 18 respiratory motion monitoring,18, 19, 20, 21, 22, 23 functional imaging correlation,24, 25, 26 and faster imaging techniques have resulted in several delivery methodologies to decrease the impact of lung motion. Another approach to reducing the impact is to minimize the motion itself by incorporating compression belts27 to restrict diaphragm contraction and expansion, implementing breath hold techniques23, 28, 29, 30 or gating the treatment by restricting delivery to particular components of the breathing cycle 14, 20, 25, 31, 32.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to reducing the impact is to minimize the motion itself by incorporating compression belts27 to restrict diaphragm contraction and expansion, implementing breath hold techniques23, 28, 29, 30 or gating the treatment by restricting delivery to particular components of the breathing cycle 14, 20, 25, 31, 32. Recent works from several research groups have also investigated the tracking of tumor by dynamic correction of MLC positions 33, 34, 35, 36, 37.…”
Section: Introductionmentioning
confidence: 99%
“…Doing so necessitates many interruptions of the beam, which results in significantly increased treatment time. To compensate for this limitation, the idea of coupling respiratory gating with a fast delivery technique, such as volumetric‐modulated arc therapy (VMAT), has increasingly been adopted as the treatment of choice for moving tumors in the liver and the pancreas 5 , 6 , 7 , 8 . In addition, the new advancements in flattening filter‐free mode (FFF) for modulated treatments allow for an increased dose rate, thus significantly reducing the treatment time for treatments delivering high doses per fraction, such as stereotactic ablative radiation therapy (SABR) (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (5) and Choi et al (6) investigated the geometric accuracy of gated VMAT using kV imaging and a dynamic phantom. Respiratory motion during intensity modulation, such as IMRT or VMAT, presents an additional challenge over 3D conformal therapy as dose gradients are no longer limited to the edges of the field and vary with time.…”
Section: Introductionmentioning
confidence: 99%